2019
DOI: 10.1111/flan.12393
|View full text |Cite
|
Sign up to set email alerts
|

Engineering engagement: Perceived L2 development and short‐term service learning abroad

Abstract: The current study compared perceived language gains between learners of different preprogram proficiencies, academic interests, and genders who participated in the same predeparture preparation and short‐stay service learning program abroad. L2 learners studying Spanish and computer science students participated in a semester‐long program to design two 1‐week technology summer camps for middle school students in the Dominican Republic, followed by a sojourn to the site where participants led all camp learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Participants were eight ( N = 8) learners of French selected from 14 students in an SA program in Paris, France, who consented to participate in the research. The selection was conditioned by an Intermediate proficiency criterion to control for similarity in predeparture proficiency (Gaugler & Matheus, 2019). This was determined via a pre‐SA 20‐to‐30‐min ACTFL Oral Proficiency Interview (OPI) administered by a certified tester, subsequently blindly, independently, and anonymously re‐rated by a second certified tester.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants were eight ( N = 8) learners of French selected from 14 students in an SA program in Paris, France, who consented to participate in the research. The selection was conditioned by an Intermediate proficiency criterion to control for similarity in predeparture proficiency (Gaugler & Matheus, 2019). This was determined via a pre‐SA 20‐to‐30‐min ACTFL Oral Proficiency Interview (OPI) administered by a certified tester, subsequently blindly, independently, and anonymously re‐rated by a second certified tester.…”
Section: Methodsmentioning
confidence: 99%
“…Research has found that SA does not always lead to expected proficiency gains (Kinginger, 2013;Tseng et al, 2021;Tullock & Ortega, 2017). While some inconsistencies can be attributed to differences in research methodology (Tullock & Ortega, 2017), various factors can influence proficiency development, including predeparture proficiency, gender (Gaugler & Matheus, 2019), motivation (Isabelli-García et al, 2018), living arrangement (Kinginger & F I G U R E 1 Example of Can-Do statements.…”
Section: Factors Impacting Proficiency During Samentioning
confidence: 99%
See 1 more Smart Citation
“…Exemplar: One type of SA program that is commonly associated with developing one's skills as a global citizen as well as an L2 speaker is international service learning-that is, community involvement abroad combined with academic study (Gaugler & Matheus, 2019). Research on service learning abroad and its potential to promote L2 learning has grown in recent years.…”
Section: Critical Global Citizenshipmentioning
confidence: 99%
“…247–248, italics added). Emotional engagement and intensive relationships emerged in a broad array of settings, including homestays, but also shared lodging, workplaces, recreational affinity spaces (see also, e.g., Fukada, ; Gaugler and Matheus, ; Kinginger & Wu, ; Zeng, ).…”
Section: Review Of Literaturementioning
confidence: 99%